Revisiting operations strategy for competitiveness: Exploring potential research opportunities - Chebo, Abdella Kosa; Endeshaw, Berhanu; Haile, Robel; Dhliwayo, Shepherd (Edelweiss Applied Science and Technology, 2024)
Operations strategy for competitiveness have been the subject of extensive and developed research. Despite the topic's wider applicability, there is a lack of a thorough understanding of the conceptual connections and effects of the field in this dynamic business environment. It is therefore appropriate to assess its progression and shape a possible future direction. Through scientific mapping and thematic progression, this study synthesizes existing research and proposes paths to advance the operations strategy for competitiveness research. The study reveals earlier, deeply researched themes like operations research, quality assurance, and strategic planning as well as more recent topics that have attracted scholars' interest, like decision-making, sustainability, cost- and profit-optimization, and investments in environmental management. In addition, the key themes are organized into five categories: manufacturing and competition, supply chain management, costs, decision-making, and sustainable development. Generally, this study offers a comprehensive resource to acquire knowledge about the recent advancements, trends, and future paths of operation strategy and competitive advantage.